2021
DOI: 10.3390/coatings11080922
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Applications of Pectin in Food, Biomedical, and Pharmaceutical Industry: A Review

Abstract: Pectin is a biocompatible polysaccharide with intrinsic biological activity, which may exhibit different structures depending on its source or extraction method. The extraction of pectin from various industrial by-products presents itself as a green option for the valorization of agro-industrial residues by producing a high commercial value product. Pectin is susceptible to physical, chemical, and/or enzymatic changes. The numerous functional groups present in its structure can stimulate different functionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(98 citation statements)
references
References 138 publications
0
62
1
1
Order By: Relevance
“…In addition, the contents of uronic acid in PAP2, PAP3, and PAP4 were 6, 6, and 8.93%, respectively. The monosaccharide profiles of the three acid polysaccharides were different from those of pectin and coconut polysaccharides in other studies ( 24 , 25 ). The above results showed that there were significant differences not only in the monosaccharide spectrum between neutral polysaccharides and acidic polysaccharides but also in the monosaccharide spectrum among the three acidic polysaccharides ( 26 ).…”
Section: Resultscontrasting
confidence: 76%
“…In addition, the contents of uronic acid in PAP2, PAP3, and PAP4 were 6, 6, and 8.93%, respectively. The monosaccharide profiles of the three acid polysaccharides were different from those of pectin and coconut polysaccharides in other studies ( 24 , 25 ). The above results showed that there were significant differences not only in the monosaccharide spectrum between neutral polysaccharides and acidic polysaccharides but also in the monosaccharide spectrum among the three acidic polysaccharides ( 26 ).…”
Section: Resultscontrasting
confidence: 76%
“…Pectin, a structural non-toxic anionic polysaccharide contained in the cell walls of many fruits, is used in the food industry as a thickening and stabilizing agent [14]. The monomer is galacturonic acid containing methylated ester groups [15,16]. The extent of methylated groups (DE) classifies it as either low methoxyl pectin (DE < 50) and high methoxyl pectin (DE > 50) [17].…”
Section: Introductionmentioning
confidence: 99%
“…These polysaccharides are water soluble and show excellent thickening, gelling properties, hydration capacity, and swelling. For these peculiar properties, they are used as an additive or ingredient for food in the preparation of jellies, jams, and marmalades but also in the pharmaceutical industry [126]. The richest source of pectins are citrus fruits peel, in particular lemon peel [127,128] but also apple pomace [129] and mango peel [130].…”
Section: High-value Added Compounds From Fruit Waste and Biological Propertiesmentioning
confidence: 99%